The Impact of Online Games on Student’s Religiosity - Maharani, Chehra Nabilah (Indonesian Journal of Islamic Education and Local Culture, 2024)
This research aims to gather sufficient information about the impact of online gaming on the religiosity of university students. This research method is a literature study that collects several previous studies to answer the impact of online games on a person's religiosity, especially a student. The results of this study indicate that there are changes regarding decreasing someone's religiosity caused by an addiction to playing online games, which results in negligence in performing obligations as Muslims. The suggestions given are to develop strategies to reduce the negative impact of online games, such as paying attention to playing time according to obligations and needs and using online games as a tool to build abstract thinking skills.